Empirical Research on the Relationship Between China Export and New Energy Consumption - Li, Lili (International Journal of Energy Economics and Policy, 2014)
With the development of the reform and opening-up, China’s volume of export trade has grown rapidly; meanwhile the new energy consumption has risen vigorously. Export trade plays extremely important role in China’s national economy, and consumption of clean energy provides significant support to China’s export. Cointegration analysis of new energy consumption is adopted based on the data from 1979 to 2011, with the result showing that there exists bi-directional Grand causal relationship between China’s export trade and new energy consumption. According to the impulse response and variance decomposition, the contribution of exports to consumption of new energy is more than that of new energy consumption to export trade. Keywords: New energy consumption; Export trade; Grand Causal relationship; Impulse response; Variance decomposition JEL Classifications: C32; Q43